(untitled) (Jurnal Sustainable, 2023)
One of the centers of educational establishments that place a high value on Islamic law’s principles are Islamic boarding schools. In order to provide their children with a high-quality Islamic education, a growing number of parents are considering enrolling them in Islamic boarding schools. However, there are still a lot of santri guardians who are concerned that their children won’t be used to living on their own because they will be far from home. Particularly the first-time female students, who have only recently experienced the educational environment of an Islamic boarding school that is distinct from their activities at home. As a result, Islamic boarding schools give new students special guidance to help them adjust well. Campus 2 Gontor Putri creates educational programs that support the coaching process by instilling contemporary pesantren values through exemplary methods, habituation, and advice utilizing a wide range of activities from the core curriculum to extracurricular and intracurricular activities. The motivation of educators, including parents, homeroom teachers, accompanying teachers, sub-district heads, and comrades in arms, is the first of several factors that support these programs. The creation of a conducive educational environment is the third, and the second is qudwah hasanah from all coaching components.